2014
DOI: 10.5194/acpd-14-13133-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial–temporal variations, sources, and transport of airborne inhalable metals (PM<sub>10</sub>) in urban and rural areas of northern China

Abstract: <p><strong>Abstract.</strong> Atmospheric particle pollution is a serious environmental issue in China, especially the northern regions. Ambient air loadings (ng m<sup>&amp;minus;3</sup>), pollution sources and apportionment, and transport pathways of trace (Cd, Co, Cu, Ni, Pb, V, and Zn) and major (Al, Ca, Fe, and Mg) metals associated with inhalable particulate matters (PM<sub>10</sub> aerosols) were characterized in urban, rural village, and rural field areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…In fact, coal for electricity generation and for domestic cooking and heating accounts for approximately 70% of the China national energy budget, thereby large amounts of HMs are emitted due to the ''concentrating effect'' while burning. Supported by such type of findings (Luo et al, 2014), it could be concluded that, after the phase-out of leaded gasoline from 1997, the principal anthropogenic source for both airborne and soil Pb in mainland China is coal combustion rather than vehicle exhaust.…”
Section: Pb Isotopic Characterization and Source Apportionmentmentioning
confidence: 90%
See 4 more Smart Citations
“…In fact, coal for electricity generation and for domestic cooking and heating accounts for approximately 70% of the China national energy budget, thereby large amounts of HMs are emitted due to the ''concentrating effect'' while burning. Supported by such type of findings (Luo et al, 2014), it could be concluded that, after the phase-out of leaded gasoline from 1997, the principal anthropogenic source for both airborne and soil Pb in mainland China is coal combustion rather than vehicle exhaust.…”
Section: Pb Isotopic Characterization and Source Apportionmentmentioning
confidence: 90%
“…For further source apportionment of HMs in different soil layers, the receptor model APCS-MLR (Luo et al, 2014) was then used to estimate the contributions (%) of various anthropogenic sources for each metal. The APCS method enabled categories of the major pollution sources to be identified along with the quantitative contributions of each source to pollutant species (Thurston et al, 2011).…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
See 3 more Smart Citations